Honoring Guests in Community Life: Study of Takhrij and Hadith Syarah - Azkiah, Hafizah Irfani; Inayatussabiila, Dhia (Journal of Takhrij Al-Hadith, 2023)
This study aims to discuss the hadith about honoring guests. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about honoring guests in Muslim history No. 47. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma’mul bih for the practice of Islam. This study concludes that the hadith of Muslim history is No. 47. It is relevant to be used as motivation, guidance, effort, and development in honoring guests in social life, especially Muslims.